IDENTIFICATION OF DEFECTS IN THE OUTSOLE MANUFACTURING PROCESS OF REBECA ARTICLES USING SIX SIGMA ANALYSIS AT PT XYZ DKI JAKARTA - Dede Dewi Soniastri; Abimanyu Yogadita Restu Aji (Politek ATK Yogyakarta Press, 2024)
PT XYZ located in DKI Jakarta is a company operating in the footwear sector. In the production process in the outsole section in Rebeca's article, several problems were found, namely dirty outsole, bubbled outsole, creeping outsole, and holey outsole. The aim of this research is to identify the factors that cause outsole defects in Rebeca's articles and to find out the results of the identification in an effort to reduce outsole defects in Rebeca's articles. The method for carrying out this research uses the Six Sigma method. The results of identifying the outsole of the Rebeca article show that based on the DPMO calculation of the outsole defect in the Rebeca article, an average DPMO value of 306.25 was obtained with a sigma level value of 4.94. This shows that the outsole production process has a capacity above the average level. sigma, but this has not achieved the target of improving the quality of Six Sigma, namely reaching a Sigma level of 6 Sigma. Proposed improvements that can be given to the factors that cause defects that occur in the outsole.